2011
DOI: 10.1016/j.neulet.2011.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Serum brain-derived neurotrophic factor and clozapine daily dose in patients with schizophrenia: A positive correlation

Abstract: Brain-derived neurotrophic factor (BDNF) plays a critical role in neurodevelopment and neuroplasticity. Altered BDNF signaling is thought to contribute to the pathogenesis of schizophrenia (SZ) especially in relation to cognitive deficits. Clozapine (CLZ) has been shown a beneficial effect on cognition in SZ in some studies and a detrimental effect in others. To examine serum BDNF, two groups of chronically medicated DSM-IV SZ patients (n=44), on treatment with clozapine (n=31) and typical antipsychotics (n=13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…For example, some studies have found a differential regulation of BDNF mRNA expression in the rat hippocampus and neocortex by typical and atypical antipsychotic administration (Bai et al, 2003), with the atypical antipsychotics olanzapine and quetiapine enhancing BDNF expression (Rizos et al, 2008). Furthermore, serum BDNF levels were higher in chronic schizophrenia patients on clozapine or typical antipsychotics than risperidone , and BDNF levels were positively associated with daily clozapine doses in patients with schizophrenia (Pedrini et al, 2011). However, some longitudinal studies have reported that lower serum BDNF levels did not increase after several weeks of antipsychotic treatment (Pirildar et al, 2004;Yoshimura et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have found a differential regulation of BDNF mRNA expression in the rat hippocampus and neocortex by typical and atypical antipsychotic administration (Bai et al, 2003), with the atypical antipsychotics olanzapine and quetiapine enhancing BDNF expression (Rizos et al, 2008). Furthermore, serum BDNF levels were higher in chronic schizophrenia patients on clozapine or typical antipsychotics than risperidone , and BDNF levels were positively associated with daily clozapine doses in patients with schizophrenia (Pedrini et al, 2011). However, some longitudinal studies have reported that lower serum BDNF levels did not increase after several weeks of antipsychotic treatment (Pirildar et al, 2004;Yoshimura et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BDNF/TrkB(tyrosine kinase B is a receptor of BDNF) signal plays an important role in learning and memory [1]. BDNF expression can increase the amount of synaptic plasticity and facilitate learning and memory formation [2][3][4]. It also promotes neuron development especially hippocampal neurogenesis and promotes cell survival, differentiation, growth, and regeneration [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…61,62 Mood stabilizers and antipsychotics are known to induce increases in the neurotrophic factors, and in particular BDNF, in BD [63][64][65] and schizophrenia. 66 In line with this, it is possible that the additional negative impact of the elevated BMI may have been overcome by optimal pharmacological treatment provided to the patients, and it could be the reason why we were unable to detect a potentially negative effect of obesity on cognitive functioning in patients in our analyses. However, as we have not collected serum samples for BDNF levels in all our subjects, we are unable to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 77%